The Pharmacology And Phytochemistry Study Of Mahogany Seeds - Geetha, Sahgal (2011)
Swietenia mahagoni which belongs to the Meliaceae family has been applied in folk medicine. To date there are no report or articles that published on the Malaysian origin S. mahagoni seeds. Therefore, this research was designed to investigate the pharmacological efficacy of S.mahagoni seeds for phytochemical analysis, antimicrobial, antioxidant, analgesic activities and for toxicity screening. The phytochemical analysis exhibited the presence of terpenoids, saponins, volatile oils, alkaloids, antraquinones, and cardiac glycosides as major active constituents. Acute oral toxicity evaluation exhibited the LD50 was relatively greater than 5000 mg/kg. This shows that, SMCM seed extract may contain potential therapeutic bioactive which is free from toxic effects. Antimicrobial activity of SMCM seed extract against Gram positive and Gram-negative bacteria and fungus strains was undertaken. The extract was found to be more active against Candida albicans. SMCM seed extract is effectively active for in vitro and in vivo anti-Candida activity against C. albicans. The SMCM seed extract was evaluated for antioxidant and analgesic activities and found to possess moderate antioxidant activity and analgesic activity at tested higher dose. SMCM seed extract shows good anti-Candida activity. Therefore, further work was undertaken to identify the possible bioactives for the anti-Candida activity. A terpenoid bioactive group was found to be active against C. albicans in bioautography assay with MIC value of 150 μg/mL. The FTIR analysis of SM Sp1 showed almost comparable stretching groups with an identified compound Swietmanin J. Our findings showed that, SMCM seed extract possess therapeutic property for anti-Candida activity. These findings could assist the herbal drug development in Malaysian biotechnology and pharmaceutical industry. Therefore, in future, further works on isolation and characterization of the pure anti- Candida bioactive are recommended. From the overall findings, the most promising activity of the SMCM seed extract was observed in its anti-Candida activity.